2022
DOI: 10.1002/anie.202116078
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorogenic Iridium(III) bis‐Tetrazine Complexes for Bioorthogonal Peptide Stapling, Bioimaging, Photocytotoxic Applications, and the Construction of Nanosized Hydrogels

Abstract: The dual functionality of 1,2,4,5-tetrazine as a bioorthogonal reactive unit and a luminescence quencher has shaped tetrazine-based probes as attractive candidates for luminogenic labeling of biomolecules in living systems. In this work, three cyclometalated iridium(III) complexes featuring two tetrazine units were synthesized and characterized. Upon photoexcitation, the complexes were non-emissive but displayed up to 3900-fold emission enhancement upon the inverse electron-demand Diels-Alder (IEDDA) [4+2] cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Complex 72b exhibits higher photocytotoxic activity toward HeLa cells containing BCN-modified HaloTag protein (IC 50,light = 0.26 μM) than those with unmodified and TCO-modified HaloTag protein (IC 50,light = 0.68 and 1.00 μM, respectively). Iridium­(III) complexes featuring two tetrazine units ( 73 ) have been developed as phosphorogenic bioorthogonal probes for bis-cyclooctynylated substrates . These complexes show extremely weak emission and 1 O 2 photosensitization (Φ Δ = 0.02–0.07) due to the tetrazine moiety, but react very rapidly with substrates carrying two BCN motifs to give bis-pyridazine conjugates with significantly enhanced emission ( I / I o = 1008.2–3885.7) and 1 O 2 generation (Φ Δ = 0.62–0.77), rendering them promising activatable bioimaging reagents and phototherapeutic agents.…”
Section: Photofunctional Transition Metal Complexes As Phototherapeut...mentioning
confidence: 99%
“…Complex 72b exhibits higher photocytotoxic activity toward HeLa cells containing BCN-modified HaloTag protein (IC 50,light = 0.26 μM) than those with unmodified and TCO-modified HaloTag protein (IC 50,light = 0.68 and 1.00 μM, respectively). Iridium­(III) complexes featuring two tetrazine units ( 73 ) have been developed as phosphorogenic bioorthogonal probes for bis-cyclooctynylated substrates . These complexes show extremely weak emission and 1 O 2 photosensitization (Φ Δ = 0.02–0.07) due to the tetrazine moiety, but react very rapidly with substrates carrying two BCN motifs to give bis-pyridazine conjugates with significantly enhanced emission ( I / I o = 1008.2–3885.7) and 1 O 2 generation (Φ Δ = 0.62–0.77), rendering them promising activatable bioimaging reagents and phototherapeutic agents.…”
Section: Photofunctional Transition Metal Complexes As Phototherapeut...mentioning
confidence: 99%
“…Over the past decade, plenty of studies reported applications of materials relied on the employ of tetrazine bioorthogonal reactions 9,25 Mostly abundant applications in this field should refer to the preparation of biologically functionalized hydrogels for therapeutic, diagnostic, and target molecule delivery applications. 26–31 Those studies mainly depended on the Diels–Alder ligation between 1,2,4,5-tetrazine and various dienophiles, especially the trans -cyclooctene (TCO) derivatives. Alternatively, a novel photocatalytic activating technique depending on the conversion of the inactivated tetrazine motif, dihydrotetrazine, to activated tetrazine for hydrogel formation was designed.…”
Section: Tbc Functions As a Robust Tool For The Preparation And Modif...mentioning
confidence: 99%
“…To date, it is still far from well recognized that a significant opportunity exists in implementing bioconjugation: that is, to tailor the structural and functional diversity of small molecules beyond establishing a robust connection with biomolecules. 9–11 Such recognition is particularly relevant to fabricating porphyrin bioconjugates for diagnostic or therapeutic purposes, as described in this work.…”
Section: Introductionmentioning
confidence: 99%